PENGARUH KEMANDIRIAN BELAJAR DAN KESIAPAN BELAJAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI SISWA IPS KELAS XI SMA YLPI PEKANBARU - T.Suhaila T.Suhaila; Henny Indrawati; Hardisem Syabrus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research purpose to determine whether there is significant influence either simultaneously or partial between independence learning and readiness learning result on the economic lesson of XI IPS student’s class of YLPI high school Pekanbaru. Population in this research is students on XI IPS class which amount 41 people, sampling in thus population using the technique until saturated that is where the entire population become sample that amount to 41 people. Data in this research is primary data and secondary data. The data collection method is through inquiries and documentation, data analysis method in this research consist of a quantitative analysis descriptive, analysis of regressing doubled linear and analysis of coefficient determination test (R2). Research result showing that independence learning are influential on the learning result of students with significant value 0,000 < 0,005, readiness learning are significant influential with significant value 0,000 < 0,005. In simultaneously the are influental significant between learning independence and readiness learning with learning result it is showned by significant value 0,000 < 0,005. Mean while coefficient determination value (R2) 0,713 it is mean explain variabel ability of independence learning and readiness learning in explain learning outcomes result variabel amount to 71,3% while the rest 28,7% influences by another free variable which is not been discussed in this research.Keyword: Learning Independence, Learning Readiness, Learning outcomes